Navigating the Digital Shift: Assessing Skills, Training, and Resources for Virtual Reference Librarians - Maesaroh, Imas; Mujib, Abdul; Kholis, Nur (Program Studi Ilmu Perpustakaan UIN Alauddin, 2025)
This study aims to identify essential skills and competencies required for VRLs, examine available training and professional development opportunities, and assess the impact of online resources and digital databases on virtual reference services. Employing a qualitative research design through library research, the study reviews relevant literature to map the skillset needed for VRLs in the digital era. The findings revealed a comprehensive range of required competencies, including technological proficiency, effective information retrieval, strong communication abilities, and a customer-service orientation. Furthermore, the study highlighted the importance of ongoing professional development through structured training programs, workshops, and self-directed learning using digital platforms. The use of online databases and digital resources was shown to enhance the effectiveness and responsiveness of virtual reference services. The research concludes that for VRLs to thrive in the digital age, they must cultivate a diverse skill set, engage in continuous professional development, and leverage available digital tools to deliver high-quality library services. These findings offer valuable insights for library institutions in designing training models and support systems that empower VRLs to meet evolving user expectations in virtual environments.